SISTEM INFORMASI AKADEMIK (SUB SISTEM : KEMAHASISWAAN DAN PENJADWALAN) (STUDI KASUS : FAKULTAS TEKNIK UNIVERSITAS HALU OLEO) - Muhammad Usgan; Ika Purwanti Ningrum; Statiswaty Statiswaty (semanTIK, 2016)
The purpose of this research is to build and design an information system called as Academic Information System Of Halu Oleo University. System that built by the author focus on processing data related to college students, determining academic advisor, GPA statistic and scheduling management.The author using Rational Unified Process (RUP) as the system development method and Unified Modeling Language (UML) as the system modeling language. This system has gone through several stages of testing and was able to interact well with the users. For example, system will issue a warning when the users successfully inputting a data or when an error occurs.   Keywords— Scheduling, Student, Unified Modeling Language (UML), Rational Unified Process (RUP)